IMPLEMENTASI MANAJEMEN PEMBELAJARAN AL-QUR’AN DI SEKOLAH DASAR ISLAM TERPADU NURUL ISHLAH BANDA ACEH - Erna Supiani; . Murniati; Nasir Usman (Jurnal Pencerahan, 2016)
The effective and efficient Qur’an learning management is a supporting factor to achieve the goal of learning the Qur’an in school in order to produce Qur’anic generation. The purpose of this study was to find out the planning, implementation, evaluation, and obstacles in learning the Qur’an at the Nurul Ishlah Integrated Islamic Elementary School (SDIT Nurul Ishlah) of Banda Aceh.This study used the descriptive method with a qualitative approach. The techniques of data collection were the interview, observation, and documentation. The subjects of this study were principal and Qur’anic teachers at the SDIT Nurul Ishlah.The results of the study were: (1) the planning was formulated by teachers based on the curriculum set by the school, but some teachers were not able to plan effectively in the learning; (2) The implementation of learning the Qur’an applied by SDIT Nurul Ishlah was in accordance with activities planned, the teachers gave motivation to the students by using various methods and learning media starting from beginning the activity with praying and revising memorization of the Qur’an classically. In main activity, the students performed their memorization to the teachers individually, then the students revised their memorization and learned the memorization of surah individually, and in final activity, the teachers gave motivation to the students to revise their memorization at home by showing motivation videos of children who love Qur’an. However, some students could not finish the tasks given by the teachers; (3) the evaluation was carried out by written exam and practice exam of reading and memorizing the Qur’an by assessing the quality of reciting, pronunciation, tajweed, and fluency, but some students could not perform their memorization fluently; (4) the obstacle faced by the teachers was the lack of motivation and interest of students to revise their memorization that made the learning quality was not improved